One-pot construction of cellulose-gelatin supramolecular hydrogels with high strength and pH-responsive properties. (15th September 2018) - Lu, Qilin; Zhang, Songhua; Xiong, Mingcheng; Lin, Fengcai; Tang, Lirong; Huang, Biao; Chen, Yandan
Highlights: Supramolecular hydrogels with high strength and pH-sensitivity were constructed. Cyclic freezing-thawing played a crucial role in the formation of hydrogel. The synergy of hydrogen bonding and CNF induced the superior mechanical performance. The one-pot route does not involve crosslinking agents or intermediate purification. A straightforward green route to prepare biopolymer-based hydrogel is presented. Abstract: Inspired by the supramolecular structure of cellulose, cellulose-gelatin supramolecular hydrogels with high strength and pH-sensitivity were constructed in a basic-based solvent system, ethylene diamine/potassium thiocyanate (EDA/KSCN) with the aid of cyclic freezing-thawing. The investigation on the characteristics of supramolecular hydrogels revealed that repeated freezing-thawing cycles played an important role in the formation of the physical cross-linked supramolecular network structure between cellulose and gelatin. The mechanical properties of supramolecular hydrogels were much higher than pure cellulose and gelatin hydrogel, and the compressive strength was 9.6 times higher than that of pure gelatin hydrogel. The synergistic effect between hydrogen-bonding interaction and the reinforcement of regenerated cellulose nanofibrils (CNF) contributed to the superior mechanical performance. Furthermore, the swelling kinetics tests showed that the supramolecular hydrogels exhibited excellent pH-responsibility, indicating potential applications in biomedical fields. Thus, a straightforward route to construct natural polymer-based hydrogels with supramolecular structure through physical crosslinking strategy without employing hazardous crosslinking agents was developed, paving the way for the design of new types of hydrogels.